2021
DOI: 10.1177/15266028211067733
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Treatment of Aortic Pathologies in Patients With Marfan Syndrome: Single-Center Experience

Abstract: Objectives: To study the outcome of endovascular treatment of aortic pathologies in patients with Marfan syndrome (MFS) at a single institution. Methods: Consecutive MFS patients who underwent endovascular repair or hybrid procedures for aortic pathologies from January 2010 to May 2020 were identified. Several endovascular and hybrid strategies have been used. Technical success, short- and mid-term survival, complications, and re-interventions were retrospectively analyzed. Results: During the study period, 24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…[30][31][32][33] In accordance with previous reports of endovascular treatment of thoracic, thoracoabdominal, and abdominal aortic disease in patients with CTD, the primary technical success was excellent in the EVICTUS cohort. [34][35][36][37][38][39] The perioperative mortality and morbidity were acceptable for patients with Marfan syndrome or Loeys-Dietz syndrome, especially given that compared with the reports of open surgery, this cohort featured patients with an older median age and more patients emergently treated for complicated dissections, as well as symptomatic or ruptured aneurysms. These results are also consistent with a recent report of thoracic endovascular repairs in patients with CTD of similar age with an analogous proportion of emergent procedures.…”
Section: Discussionmentioning
confidence: 99%
“…[30][31][32][33] In accordance with previous reports of endovascular treatment of thoracic, thoracoabdominal, and abdominal aortic disease in patients with CTD, the primary technical success was excellent in the EVICTUS cohort. [34][35][36][37][38][39] The perioperative mortality and morbidity were acceptable for patients with Marfan syndrome or Loeys-Dietz syndrome, especially given that compared with the reports of open surgery, this cohort featured patients with an older median age and more patients emergently treated for complicated dissections, as well as symptomatic or ruptured aneurysms. These results are also consistent with a recent report of thoracic endovascular repairs in patients with CTD of similar age with an analogous proportion of emergent procedures.…”
Section: Discussionmentioning
confidence: 99%
“… 35 In cases already submitted to open repair, allowing for proximal or proximal and distal landing zones in synthetic grafts, endovascular repair may be a good option by overcoming this limitation. 35 36 Clough et al 35 showed that this strategy was both feasible and safe, although more mid- and long-term follow-up is needed to correctly assess durability of these repairs. Connective tissue disease patients are frequently burdened with multiple reinterventions, which significantly impairs their quality of life via anxiety related to surgeries, which may lead them to seek less invasive options.…”
Section: Endovascular Repair Of Late Thoracic and Thoracoabdominal Ao...mentioning
confidence: 99%
“…Data on F/BEVAR for TAAAs related to connective tissue disorders are still lacking. Only a few studies with limited numbers have been published [99][100][101]. In a recent literature review [102], 26 patients with TAAAs related to connective tissue disorders and treated by F/BEVAR could be identified.…”
Section: Connective Tissue Diseasementioning
confidence: 99%